The Interior Design of a Women’s Health and Beauty Center with Postmodern Style in Surakarta City - Putri Widyaningrum; Joko Budiwiyanto (Institut Seni Indonesia Surakarta, 2021)
The Interior Design of a Women’s Health and Beauty Center in Surakarta City, precisely in a building of fitness and beauty center, applies a postmodern style. This design aims to create the interior design of a Women’s Health and Beauty Center in Surakarta City which is able to facilitate all activity needs in comfortable and safe ways, and provides excellent beauty care and body fitness services. The interior design of a Women’s Health and Beauty Center adopts Kurtz's programming method consisting of orientation stages, basic program creation, programming repetition, until the design reaches approval. The design foundation used is the aesthetic, ergonomic, and functional approaches. This design, with eclectic concept, is objected to gain attraction from the visitors by the creation of a space with a post-modern style that presents the theme of parang batik motifs. Surakarta's local wisdom in the form of such batik motifs aligned with modern elements with tropical nuances will answer the typical Indonesian comfort within several spaces, including: Main Lobby, Fitness Area Lobby, Gymnastics Studio, Fitness, Beauty Area Lobby, Whirlpool Room, Day Spa Room, Facial Treatment Room, Pedicure &Manicure Room, and Sauna Room.